Survey of VPU olympiad for young mathematicians - Jakaitytė, Eglė; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2009)
The article presents problems of VPU Young Mathematicians‘ Olympiad 2009, their solution and a short statistical anglysis of Lithuanian Olympiad movemenr of mathematicians.